Evaluation of chronic periapical lesions by digital subtraction radiography by using adobe photoshop CS: A technical report - Carvalho, Fabiola B.; Gonçalves, Marcelo [UNESP]; Tanomaru-Filho, Mdrio (Elsevier B.V., 2007)
The purpose of this study was to describe a new technique by using Adobe Photoshop CS (San Jose, CA) image-analysis software to evaluate the radiographic changes of chronic periapical lesions after root canal treatment by digital subtraction radiography. Thirteen upper anterior human teeth with pulp necrosis and radiographic image of chronic periapical lesion were endodontically treated and radiographed 0, 2, 4, and 6 months after root canal treatment by using a film holder. The radiographic films were automatically developed and digitized. The radiographic images taken 0, 2, 4, and 6 months after root canal therapy were submitted to digital subtraction in pairs (0 and 2 months, 2 and 4 months, and 4 and 6 months) choosing image, calculation, subtract, and new document tools from Adobe Photoshop CS image-analysis software toolbar. The resulting images showed areas of periapical healing in all cases. According to this methodology, the healing or expansion of periapical lesions can be evaluated by means of digital subtraction radiography by using Adobe Photoshop CS software.
Keywords: digital subtraction; periapical lesion; radiograph